Wafer-scale fabrication of high-quality tunable gold nanogap arrays for surface-enhanced Raman scattering. Issue 25 (13th June 2019) - Le-The, Hai; Lozeman, Jasper J. A.; Lafuente, Marta; Muñoz, Pablo; Bomer, Johan G.; Duy-Tong, Hien; Berenschot, Erwin; van den Berg, Albert; Tas, Niels R.; Odijk, Mathieu; Eijkel, Jan C. T.
Abstract : A robust method is developed for large-scale fabrication of high-quality tunable gold nanogap arrays at low-cost for surface-enhanced Raman scattering. Abstract : We report a robust and high-yield fabrication method for wafer-scale patterning of high-quality arrays of dense gold nanogaps, combining displacement Talbot lithography based shrink-etching with dry etching, wet etching, and thin film deposition techniques. By using the self-sharpening of <111>-oriented silicon crystal planes during the wet etching process, silicon structures with extremely smooth nanogaps are obtained. Subsequent conformal deposition of a silicon nitride layer and a gold layer results in dense arrays of narrow gold nanogaps. Using this method, we successfully fabricate high-quality Au nanogaps down to 10 nm over full wafer areas. Moreover, the gap spacing can be tuned by changing the thickness of deposited Au layers. Since the roughness of the template is minimized by the crystallographic etching of silicon, the roughness of the gold nanogaps depends almost exclusively on the roughness of the sputtered gold layers. Additionally, our fabricated Au nanogaps show a significant enhancement of surface-enhanced Raman scattering (SERS) signals of benzenethiol molecules chemisorbed on the structure surface, at an average enhancement factor up to 1.5 × 10 6 .